2016
DOI: 10.1021/acs.biochem.5b01179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Substrate Selectivity of Alkyladenine DNA Glycosylase: The Synergistic Interplay of Active Site Flexibility and Water Reorganization

Abstract: Human alkyladenine DNA glycosylase (AAG) functions as part of the base excision repair (BER) pathway by cleaving the N-glycosidic bond that connects nucleobases to the sugar-phosphate backbone in DNA. AAG targets a range of structurally diverse purine lesions using nonspecific DNA-protein π-π interactions. Nevertheless, the enzyme discriminates against the natural purines and is inhibited by pyrimidine lesions. This study uses molecular dynamics simulations and seven different neutral or charged substrates, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 78 publications
(215 reference statements)
4
27
0
1
Order By: Relevance
“…That said, with so many ribonucleotides incorporated into the genome that are susceptible to oxidative damage, it is likely there are also damaged rNMPs within the genome. For example, ribonucleotide abasic sites could be generated by either spontaneous hydrolysis of the RNA N-glycosidic bond or by glycosylase cleavage of oxidized rNMPs [11] , [63] . While the RNA glycosidic bond is stronger and, thus, less susceptible to spontaneous hydrolysis than DNA, even a small fraction of incorporated ribonucleotides becoming abasic could pose a threat to genomic stability if not repaired by APE1 [6] .…”
Section: Discussionmentioning
confidence: 99%
“…That said, with so many ribonucleotides incorporated into the genome that are susceptible to oxidative damage, it is likely there are also damaged rNMPs within the genome. For example, ribonucleotide abasic sites could be generated by either spontaneous hydrolysis of the RNA N-glycosidic bond or by glycosylase cleavage of oxidized rNMPs [11] , [63] . While the RNA glycosidic bond is stronger and, thus, less susceptible to spontaneous hydrolysis than DNA, even a small fraction of incorporated ribonucleotides becoming abasic could pose a threat to genomic stability if not repaired by APE1 [6] .…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that configurationally similar water-mediated contacts play a distinct role during the recognition process of the DNA by the transcription factors belonging to the ETS-Family. In an important recent work, Lenz and Wetmore showed the significance of the reorganizations of DNA bases and water around the active sites during the inhibition process of enzymes. Structural arrangements and energetics of the interfacial water around the Bam HI protein–DNA complex has been explored in detail using the grand canonical Monte Carlo (GCMC) method .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a combination of Monte Carlo simulations (OPLS‐AA), free energy perturbation and DFT calculations (B3LYP/6‐311++G(d,p)) revealed that AAG significantly prefers binding to Hx over canonical A, providing the first insight into the lack of canonical purine repair. Subsequently, MD (AMBER) simulations have been used to investigate differences in the AAG active site configuration upon binding seven different nucleotides, including neutral or charged substrates, inhibitors and the undamaged purines . These calculations revealed that neutral substrates share a common active site hydrogen bond with His136, which aids alignment of active site π–π interactions that are likely critical for catalysis.…”
Section: Alkyladenine Dna Glycosylasementioning
confidence: 99%